Enhanced bioconversion of hydrogen and carbon dioxide to methane using a micro-nano sparger system: mass balance and energy consumption. Issue 47 (25th July 2018) - Liu, Ye; Wang, Ying; Wen, Xinlei; Shimizu, Kazuya; Lei, Zhongfang; Kobayashi, Motoyoshi; Zhang, Zhenya; Sumi, Ikuhiro; Yao, Yasuko; Mogi, Yasuhiro
Abstract : Simultaneous CO2 removal with renewable biofuel production can be achieved by methanogens through conversion of CO2 and H2 into CH4 . However, the low gas–liquid mass transfer ( k L a ) of H2 limits the commercial application of this bioconversion. Abstract : Simultaneous CO2 removal with renewable biofuel production can be achieved by methanogens through conversion of CO2 and H2 into CH4 . However, the low gas–liquid mass transfer ( k L a ) of H2 limits the commercial application of this bioconversion. This study tested and compared the gas–liquid mass transfer of H2 by using two stirred tank reactors (STRs) equipped with a micro-nano sparger (MNS) and common micro sparger (CMS), respectively. MNS was found to display superiority to CMS in methane production with the maximum methane evolution rate (MER) of 171.40 mmol/LR /d and 136.10 mmol/LR /d, along with a specific biomass growth rate of 0.15 d −1 and 0.09 d −1, respectively. Energy analysis indicated that the energy-productivity ratio for MNS was higher than that for CMS. This work suggests that MNS can be used as an applicable resolution to the limited k L a of H2 and thus enhance the bioconversion of H2 and CO2 to CH4 .